Thermal and EPR investigations of thallium gallium disulphide single crystal - Acikgoz, M.; Mikailzade, F. A. (Wiley-V C H Verlag Gmbh, 2009)
In this research, the results of the differential scanning calorimetry (DSC) and electron paramagnetic resonance (EPR) investigations of TIGaS(2) single crystal are presented. Specific heat capacity (C(p)) anomalies of layered TlGaS(2) have been obtained by using a new DSC technique for such crystals. Remarkable heat capacity anomalies have been revealed at the temperatures of 137.7 K, 174.5 K and 238.5 K. It is found that the anomalies appear at maximum with a small deviation (by 34%) from the regular values, and CP discontinuity amounted to approximately 5%. Additionally, EPR spectra of Fe doped TIGaS(2) single crystals have been recorded at various temperatures down to 6 K for different orientations of the applied magnetic field. Transformations of present EPR spectra are not sufficient for the confirmation of structural phase transitions, in contrast to the cases in iso structural TlInS(2) and TlGaSe(2) compounds. (C) 2009 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim
Keywords: ternary compounds; heat capacity; DSC; EPR